2007
DOI: 10.1590/s0100-72032007000300008
|View full text |Cite
|
Sign up to set email alerts
|

A pesquisa do linfonodo sentinela para o câncer de mama na prática clínica do ginecologista brasileiro

Abstract: RevisãoResumo O estudo histopatológico dos linfonodos axilares continua sendo o melhor parâmetro para a avaliação do prognóstico do câncer de mama. No entanto, como em cerca de 80% das pacientes com tumores de até 2 cm os linfonodos não apresentam comprometimento neoplásico, foi proposta, há alguns anos, a dissecção do linfonodo sentinela, reduzindo a morbidade cirúrgica nas pacientes com resultado negativo. Recentemente, esta técnica cirúrgica disseminou-se no Brasil, mas existem duas questões importantes: qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
0
4
0
9
Order By: Relevance
“…In addition, they represent the first phase of the tumor's long range spreading [1]. Analysis of the lymph nodes is, therefore, one of the most relevant factors for staging mammary carcinoma in both species [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they represent the first phase of the tumor's long range spreading [1]. Analysis of the lymph nodes is, therefore, one of the most relevant factors for staging mammary carcinoma in both species [2].…”
Section: Introductionmentioning
confidence: 99%
“…Coelho-Oliveira et al, (2004) observed that in both injection techniques (peritumoral and intradermal) 100% of the SLN were localized in the axilla, independently from the lesion topography, without identifying paraesternal lymph nodes, even in the peritumoral injection group. The periareolar or subareolar injection stands out for representing a converging point of all the mammary lymphatic drainage pathways, before the axillary and internal mammary chains (Quadros and Gebrim, 2007). Barros et al (2005) verified through lymphoscintigraphy of 112 patients that in 86.6% of the cases SLN localization was in the axillary lymphonodal chain, in 8.9% in the axilla and also in the internal mammary chain, and in only 4.5% the radiopharmaceutical migrated exclusively to the internal mammary chain.…”
Section: Resultsmentioning
confidence: 99%
“…A literatura afirma que o comprometimento dos linfonodos permanece como principal fator de recidivas e metástases, sendo indicativos de pior prognóstico, sendo que tumores de até 10 mm de diâmetro apresentam possibilidade de 10% a 15% de comprometimento linfonodal axilar enquanto tumores entre 1,1 e 2,0 cm apresentam o comprometimento de 30%. 28,29 Tendo como base os resultados descritivos, a análise dos dados deste estudo demonstrou que os métodos avaliados apresentaram concordância geral de 86,15%. Esses achados são concordantes com Siqueira et al (2006), em trabalho similar.…”
Section: Us Mmgunclassified